Online Information Exchanges for Parents of Children With a Rare Health Condition: Key Findings From an Online Support Community - Oprescu, Florin; Campo, Shelly; Lowe, John; Andsager, Julie; Morcuende, Jose A (JMIR Publications, 2013)
BackgroundThe Internet provides new opportunities for parents of children with difficult illnesses and disabilities to find information and support. The Internet is particularly important for caregivers of children with special needs due to numerous health-related decisions they face. For at-risk populations, online support communities can become key settings and channels for health promotion and communication. ObjectiveThis study is an initial exploration of the information-seeking and information-provision processes present in an online support community, which is an area of opportunity and interest for Internet-based medical research and practice. The aim of this study was to explore and describe information-related processes of uncertainty management in relationship to clubfoot. Specifically, the study explored interpersonal communication (information seeking and provision) in an online support community serving the needs of parents of children with clubfoot. MethodsThe study population consisted of messages posted to an online community by caregivers (parents) of children with clubfoot. The theoretical framework informing the study was the Uncertainty Management Theory (UMT). The study used content analysis to explore and categorize the content of 775 messages. ResultsWomen authored 664 of 775 messages (86%) and men authored 47 messages (6%). Caregivers managed uncertainty through information seeking and provision behaviors that were dynamic and multilayered. The ratio of information-seeking messages to information-provision responses was 1 to 4. All five types of information-seeking behaviors proposed by Brashers' schema were identified, most of them being correlated. Information seeking using direct questions was found to be positively correlated to self-disclosure (r=.538), offering of a candidate answer (r=.318), and passive information seeking (r=.253). Self-disclosure was found to be positively correlated to provision of a candidate answer (r=.324), second-guessing (r=.149), and passive information seeking (r=.366). Provision of a candidate answer was found to be positively correlated with second-guessing (r=.193) and passive information seeking (r=.223). Second-guessing was found to be positively correlated to passive information seeking (r=.311). All correlations reported above were statistically significant (P<0.01). Of the 775 messages analyzed, 255 (33%) identified a medical professional or institution by name. Detailed medical information was provided in 101 (13%) messages, with the main source of information identified being personal experience rather than medical sources. ConclusionOnline communities can be an effective channel for caregivers, especially women, to seek and offer information required for managing clubfoot-related uncertainty. To enhance communication with parents, health care institutions may need to invest additional resources in user-friendly online information sources and online interactions with caregivers of children with special illnesses such as clubfoot. Furthermore, explorations of information-seeking and information-provision behaviors in online communities can provide valuable data for interdisciplinary health research and practice.